2012
DOI: 10.1177/0312896212458788
|View full text |Cite
|
Sign up to set email alerts
|

Do alternative methods of reporting non-controlling interests really matter?

Abstract: Researchers have long been interested in whether the classification of various items on the balance sheet matters to investors. This paper provides evidence on whether reporting non-controlling interests (NCI) as equity or as non-equity matters in terms of value relevance. We use a sample of German firms that voluntary adopted International Financial Reporting Standards early. This adoption required them to change their reporting of NCI from the non-equity to the equity portion of the balance sheet. After cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
34
0
7

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(45 citation statements)
references
References 67 publications
4
34
0
7
Order By: Relevance
“…Using a sample of German early IFRS adopters, Lopes et al (2013) show that whether non-controlling interests are reported as equity or nonequity are priced in the same manner. They conclude that equity markets are efficient in their processing of information regardless of the influence of standard setters in mandating classifications.…”
Section: Consequences Of Accounting Standardsmentioning
confidence: 99%
“…Using a sample of German early IFRS adopters, Lopes et al (2013) show that whether non-controlling interests are reported as equity or nonequity are priced in the same manner. They conclude that equity markets are efficient in their processing of information regardless of the influence of standard setters in mandating classifications.…”
Section: Consequences Of Accounting Standardsmentioning
confidence: 99%
“…Perubahan atas teori yang dianut menyebabkan bahwa perubahan pada penyajian suatu pos dalam laporan keuangan tidak serta merta mengubah persepsi investor terhadap pos tersebut. Lopes et al (2012). Perbedaan persepsi investor terhadap lokasi suatu item keuangan menyebabkan sebagian investor harus melakukan penyesuaian terlebih dahulu ketika melakukan analisis atas laporan keuangan dan sebagian investor langsung mempertimbangkan perubahan penyajian tersebut dalam analisisnya.…”
Section: Pendahuluanunclassified
“…Dengan mengacu pada model Ohlson (1995) dan mengadopsi model penelitian Lopes et al (2012), penelitian ini menggunakan sampel sebanyak 213 perusahaan terdaftar di BEI dan periode observasi dari tahun 2008 hingga tahun 2013. Hasil penelitian menemukan bahwa perubahan lokasi penyajian kepentingan nonpengendali tidak mengubah persepsi investor.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Previous studies analyzed the di¤erent recognition of essentially the same accounting information in the same …nancial statement (Cahan et al, 2000;So and Smith, 2009). Particularly, in their investigation of NCI reporting, Lopes et al (2012) concluded that investors are not sensitive to changes in the reporting location but to the presence of NCI at all. Nevertheless, the nature of NCI as debt or equity is crucially determined by the possibility of blocking minorities due to corporate law, which might di¤er among countries.…”
mentioning
confidence: 99%